Remote Terminal Unit (RTU) Hardware Design and Implementation Efficient in Different Application - Ab Ghani, Mohd Ruddin; Mat Hanafiah, Mohd Ariff; Wan Jusoh, Wan Nor Shela Ezwane; Raman, Siti Hajar (2013)
This paper introduces the design and the development of RTU module with small remote telemetry unit suitable for different application in low voltage system. The design based on microcontroller which represents the intelligent brain of any low cost RTU. Small sizes RTU are responsible for data acquisition in substations and accomplishment of central station commands. This paper presents a new hardware design for an RTU that performs based on a PIC16F877 device operating at 20MHz and runs from a 9-24V AC/DC supply. The design is composed of four main modules with its own components in the architecture which include communication interface, analogue input, digital input and digital output. All operational tasks will be handled by non-expensive distribution automation system through it intelligent RTU by providing the best solutions without human intervention. Only Intelligent RTU together with the SCADA is capable to perform intelligent decisions on the distribution automation tasks. An intelligent Microcontroller based RTU for distribution automation system is proposed to innovate and renovate the downstream part of the power distribution system including the most advance communication networking system. This method utilizes automation concept of creating an intelligent RTU through modification and innovations.